Communication Patterns in Islamic Religious Education Learning (Evaluative Study at SMA Negeri 1 Pasaman) - Sakban Sakban; Wismanto Wismanto; Salman Salman (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
The researcher saw that the condition of students at SMA Negeri 1 Pasaman was less enthusiastic in the teaching and learning process. This problem was caused by the communication pattern of Islamic religious education learning carried out by Islamic religious education teachers. This is what encourages researchers to conduct closer research and study in depth about the communication patterns of Islamic religious education in these schools. This study aims to reveal how the communication patterns of Islamic religious education learning carried out by Islamic religious education teachers in delivering learning materials. The research method that the researcher uses is a qualitative method. This method is expected to reveal matters relating to the communication patterns of Islamic religious education teachers in the process of delivering Islamic religious education subject matter. The results of this study indicate that the pattern of communication carried out in the process of delivering Islamic religious education material at SMA Negeri 1 Pasaman is still one-way and two-way. This can be seen from various aspects that show the patterns of communication carried out by the Islamic religious education teacher which shows the communication patterns carried out by the Islamic religious education teacher. The method used in delivering Islamic religious education material is by using the lecture and question and answer methods. The method used shows that there are two communication patterns carried out by Islamic religious education teachers, namely one-way communication patterns and two-way communication patterns.